A Clinical Analysis of Risk Factors for Interstitial Lung Disease in Patients with Idiopathic Inflammatory Myopathy. (9th September 2013) - Cen, Xiaomin; Zuo, Chuan; Yang, Min; Yin, Geng; Xie, Qibing
Abstract : Interstitial lung disease (ILD) is a common and severe complication of idiopathic inflammatory myopathies (IIM). The aim of our study was to identify risk factors for ILD by evaluating both clinical and biochemical features in IIM patients with or without ILD. From January 2008 to December 2011, medical records of 134 IIM patients in our rheumatology unit were reviewed. The patients were divided into ILD group (83 patients) and non-ILD group (51 patients). The clinical features and laboratory findings were compared. The univariable analyses indicated that arthritis/arthralgia (54.2% versus 17.6%, P < 0.05 ), Mechanic's hand (16.9% versus 2.0%, P < 0.05 ), Raynaud's phenomenon (36.1% versus 2.0%, P < 0.05 ), heliotrope rash (44.6% versus 19.6%, P < 0.05 ), fever (43.4% versus 21.6%, P < 0.05 ), elevated ESR (60.2% versus 35.3%, P < 0.05 ), elevated CRP (55.4% versus 31.4%, P < 0.05 ), or anti-Jo-1 antibody (20.5% versus 5.9%, P < 0.05 ) were risk factors for developing ILD in IIM. Multivariable unconditional logistic regression analysis that showed arthritis/arthralgia (OR 7.1, 95% CI 2.8–18.1), Raynaud's phenomenon (OR 29.1, 95% CI 3.6–233.7), and amyopathic dermatomyositis (ADM) (OR 20.2, 95% CI 2.4–171.2) were the independent risk factors for developing ILD in IIM.